Impact of simulating real microplastics on toluene removal from contaminated soil using thermally enhanced air injection. (1st October 2022) - Li, Yuan; Wei, Mingli; Yu, Bowei; Liu, Lei; Xue, Qiang
Abstract: This paper investigated the impacts of various real microplastics (MPs), i.e., polyethylene (PE) and polyethylene terephthalate (PET) with different sizes (1000–2000 and 100–200 μm) and different dosages (0.5 and 5% on a dry weight basis), on the toluene removal during the thermally enhanced air injection treatment. First, microscopic tests were carried out to determine the MPs' microstructure and behavior. The PE was mainly a small block, and PET appeared filamentous and sheeted with a larger slenderness ratio. Second, the interactions between MPs and toluene-contaminated soils were revealed by batch adsorption equilibrium experiments and low-field magnetic resonance. The morphological differences and dosage of the MPs impacted soils' total porosity (variation range: 39.2–42.7%) and proportion of the main pores (2–200 μm). Third, the toluene removal during the air injection consisted of compaction, rapid growth, rapid reduction, and tailing stages, and the MPs were regarded as an emerging solid state to affect these removal stages. The final cumulative toluene concentrations of soil-PET mixtures were influenced by total porosity, and those of soil-PE mixtures were controlled by total porosity (influence weight: 0.67) and adsorption capacity (influence weight: 0.33); meanwhile, a self-built comprehensive coefficient of MPs can reflect the relationship between them and cumulative concentrations (correlation coefficient: 0.783). Graphical abstract: Image 1 Highlights: Introduced MPs are an emerging solid phase, affecting adsorption and porosity. Removal is divided into 4 stages: compaction, rapid growth, rapid reduction, tailing. Total emissions of PET mixtures are influenced by total porosity. Total emissions of PE mixtures are affected by total porosity and adsorption capacity. Cumulative emissions can be expressed quantitatively by a comprehensive coefficient.